AN ECONOMIC ANALYSIS OF TOTAL FACTOR PRODUCTIVITY (TFP) OF POTATO IN WEST BENGAL - Chatterjee, S.; Saha, M.; Samanta, M K; Mondal, S. S. (Potato Journal, 2013)
The total factor productivity growth (TFPG) analysis of potato for the state of West Bengal during 1980-81 to 2001-02 showed that the state recorded 6.19% growth of output index, 3.17% growth of input index and 2.92% growth in TFP index. The technological advancement in potato has occurred in West Bengal during the entire period.